Pelatihan program perencanaan kegiatan promosi wisata Soko Langit, Kabupaten Wonogiri - Hidayah, Nur; Febrianti, Dewi Anisa; Rahayu, Anisa Seto; Aziz, Muhammad Ibnu (Nur Science Institute, 2025)
Conto Hamlet, Bulukerto District, Wonogiri Regency, is starting to develop into a tourist village, one of which is the Soko Langit swimming pool tourist attraction, which is managed and developed by one family. This service is intended to provide knowledge about promotion through social media, which is an alternative to disseminating information, as well as providing training in the use of promotional features found on social media platforms such as Instagram and TikTok. Devotion consists of three stages, namely, preparation, implementation and monitoring. The management appreciates the service activities and feels helped so that in the future, they can be implemented to further develop the Soko Langit tourist attraction because promotion on social media platforms is felt more effective and efficient. In conclusion, the use of social media as a centre for massive information dissemination must continue to be increased, especially at tourist attractions in remote areas, so the public can more widely receive information about these tourist attractions through content uploaded on social media.